Diarrhea in Children Under Five Years Old at RSUD Kota Kendari - Tosepu, Ramadhan; A, Rachmawati.; ., Nuraisyah; Nengah Sunarto, I; Rangga Massora, Veriasari (KnE Social Sciences, 2023)
Diarrhea is the world’s biggest cause of death for children under five years old. According to UNICEF records, every second toddler dies of diarrhea. Diarrhea is often considered a trivial disease, but according to World Health Oraganization records, diarrhea kills 2 million children in the world every year. This descriptive study used a retrospective approach and utilizes data from diarrhea case reports and medical records of diarrhea patients at RSUD Kota Kendari. The research was conducted in October 2022, and the population were all children under five years old who suffered from diarrhea and had been treated at RSUD Kota Kendari. Then the data is presented in the form of tables or graphs. The results showed that diarrhea was more common in males than females. 46 cases (51.69%) were males, and 43 (48.31%) were females. The highest case of diarrhea was found in children aged 1-4 years, with 51 cases (57.30%), and the highest increase of cases occurred in August with 21 cases. More boys were hospitalized than girls. Weather can cause diarrhea. Based on the data, the highest diarrhea rate occurred in October, when the dry season peaked and the availability of clean water was low. Based on the surveyed data, children were more susceptible to diarrhea because they were still in their infancy. Therefore their immunity was still low, and their awareness of the importance of paying attention and maintaining personal hygiene was minimal. Keywords: Diarrhea, Children, Environmental Health